Don’t tell it like it is: Preserving collegiality in the summative peer review of teaching - Iqbal, Isabeau Anisa (Canadian Journal of Higher Education, 2014)
While much literature has considered feedback and professional growth in formative peer reviews of teaching, there has been little empirical research conducted on these issues in the context of summative peer reviews. This article explores faculty members’ perceptions of feedback practices in the summative peer review of teaching and reports on their understandings of why constructive feedback is typically non-existent or unspecific in summative reviews. Drawing from interview data with 30 tenure-track professors in a research-intensive Canadian university, the findings indicated that reviewers rarely gave feedback to the candidates, and when they did, comments were typically vague and/or focused on the positive. Feedback, therefore, did not contribute to professional growth in teaching. Faculty members suggested that feedback was limited because of the following: the high-stakes nature of tenure, the demands for research productivity, lack of pedagogical expertise among academics, non-existent criteria for evaluating teaching, and the artificiality of peer reviews. In this article I argue that when it comes to summative reviews, elements of academic culture, especially the value placed on collegiality, shape feedback practices in important ways.